NOBLE GASES IN NEW LUNAR METEORITES FROM OMAN: IRRADIATION HISTORY, TRAPPED GASES, AND COSMIC-RAY EXPOSURE AND K-AR AGES - Shukolyukov Yu.A.; Nazarov M.A.; Ott U. (My University, 2004)
Among numerous new meteorites found during 2001-2002 in the desert regions of the Sultanate of Oman, the achondrites Dhofar 303, Dhofar 305, Dhofar 307, Dhofar 280, Dhofar 733, and Dhofar 731 were identified as fragments of lunar rocks on the basis of mineralogical, petrological, and chemical criteria. In this paper we present new data on the lunar genesis of these meteorites, analyze the problem of pairing of these samples, determine their cosmic-ray exposure age, estimate the timing of gas retention (apparent K/Ar age), and explore the contributions of various components of trapped noble gases, both primordial and terrestrial atmospheric ones.